2015
DOI: 10.1542/peds.2014-3573
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Visits for Self-Inflicted Injuries in Adolescents

Abstract: OBJECTIVES: To describe emergency department (ED) visits for self-inflicted injury (SII) among adolescents, examine trends in SII mechanisms, and identify factors associated with increased risk.METHODS: Analyses included patients aged 10 to 18 years from the National Trauma Data Bank, years 2009 to 2012. We used Cochran-Armitage trend tests to examine change over time and generalized linear models to identify risk factors for SII. RESULTS:We examined 286 678 adolescent trauma patients, 3664 (1.3%) of whom sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 22 publications
(40 reference statements)
3
25
0
Order By: Relevance
“…Acute poisoning in children, accidental or voluntary, represents a real problem of public health with an increasing incidence (1,2). Detailed statistical data are provided by the Annual Report of the American Association of Antitoxic Centers, which in 2017 reported 645,000 poisonings in pediatric patients, of which 27% (171,303 cases) in the age group 13-18 years.…”
Section: Discussionmentioning
confidence: 99%
“…Acute poisoning in children, accidental or voluntary, represents a real problem of public health with an increasing incidence (1,2). Detailed statistical data are provided by the Annual Report of the American Association of Antitoxic Centers, which in 2017 reported 645,000 poisonings in pediatric patients, of which 27% (171,303 cases) in the age group 13-18 years.…”
Section: Discussionmentioning
confidence: 99%
“…In Ontario during 2002 to 2011, incident rates decreased between 2002/03 to 2006/07, but not thereafter, for adolescents aged 12 to 17 years [ 38 ]. In the United States, rates per 1,000 increased from 2.57 to 4.53 during 1993 to 2008 for adolescents aged 15–19 [ 39 ] while for those aged 10 to 18 years a National Trauma Data Bank study showed ED visits for self-harm increased from 2009 to 2012 [ 40 ]. Our nine-year Canadian population-based study showed the overall rate of ED visits by sex declined during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the evaluation and management of children and adolescents with acute mental health problems (comprising SITBs and suicide ideation and/or attempts), three main issues are currently debated in literature: first, children and adolescents in psychiatric crisis are seen in general pediatric or medical EDs, which are crowded, noisy, high-stimulation environments, often with long waiting times and not enough private or quiet space; [ 6 ] second, most young people presenting with a psychiatric crisis are treated by pediatric emergency clinicians and staff who lack psychiatric training, or by adult psychiatric clinicians who lack training in the diagnosis and treatment of children and adolescents; [ 5 , 6 , 14 , 15 ] third, more than half of the youths presenting to the ED after a suicide attempt or another episode of deliberate self-harm do not receive a mental health assessment. [ 16 , 17 ]…”
Section: Introductionmentioning
confidence: 99%